Dietary fish oilnormalized glucose-stimulated insulin secretion in isolated pancreatic islets of dyslipemic rats through mechanisms involving glucose phosphorylation ,peroxisome proliferator-activated receptor γ and uncoupling protein2 - Ferreira, M. R. (2013)
This study evaluates some possible mechanisms behind the beneficial effects of dietary fish oil (FO) on β cell dysfunction in rats fed a sucrose-rich diet (SRD). Rats were fed a SRD for 6 months. Thereafter, half the rats received a SRD in which corn oil was partially replaced by FO up to 8 months. The other half continued consuming the SRD up to 8 months. A control group was fed a control diet throughout the experimental period. In isolated islets of SRD-fed rats dietary FO normalized the reduced glucose phosphorylation, the altered glucose oxidation, the triglyceride content, the increased protein mass levels of peroxisome proliferator-activated receptor γ (PPARγ) and uncoupling protein 2 without changes in GLUT2 and PPARα. These finding suggest that the changes mentioned above could be involved in the normalization of the altered glucose-stimulated insulin secretion pattern in this nutritional model of dyslipidemia and insulin resistance.